Social Support, Peer Counselling and The Community Counsellor - Carty, Laurie (Canadian Journal of Counselling and Psychotherapy, 2011)
This article describes a community peer counselling program for adolescents, and an outcome research study that examined the same program. A group of adolescents who had received peer counselling was compared to two control groups in order to examine the impact of the peer counselling program on stress and social support. A-File and SSI instruments were administered. Analysis of variance and the Scheffe test of statistical analysis found significant differences between the counselled group means and both control group means on the social support scales. Posttests were given to the same subjects five months later. The paired t-test of statistical analysis found a significant difference between the pretest and posttest means in the counseled group on measures of stress, and decreases in one control group on measures of social support. Peer counselling seemed to have a positive effect on the promotion of healthy development in the young people experiencing the peer counselling program.